Gut microbiota and physical activity level: characterization from sedentary to soccer players - Petri, Cristian; Mascherini, Gabriele; Izzicupo, Pascal; Rosati, Diletta; Cerboneschi, Matteo; Smeazzetto, Serena; Arrones, Luis Suarez (Biology of Sport, 2024)
Evidence of the relationship between physical activity and gut microbiota composition is steadily increasing. The purpose of the study is to compare the gut microbiota composition of a group of elite male soccer players with a group of subjects with different physical activity levels. Cross-sectional studies were performed on 91 healthy young males, in detail: 17 elite soccer players (23.7±4.2 yrs, BMI 23.2±1.2 kg/m 2 ); 14 with high levels of physical training (24.5±5.6 yrs, BMI 22.7±0.8 kg/m 2 ); 23 with moderate levels of physical training (29.3±3.9 yrs, BMI 22.5±0.8 kg/m 2 ); and 37 healthy men without exercise habits(28.1±5.9 yrs, BMI 22.4±1.0 kg/m 2 ). Relative microbiota composition was determined by analyzing DNA extracted from stool samples. The quality and quantity of extracted DNA were assessed using a Qubit Fluorometer. Differences between subjects’ populations were analyzed using a one-way ANOVA, and Bonferroni’s post-hoc test was employed to identify localized effects. Elite soccer players and subjects with high physical activity levels showed a significantly higher prevalence of the nine microbiota populations analyzed than subjects with moderate physical training or who were sedentary. No differences were found in the Firmicutes to Bacteroidetes ratio among the different study populations. This study reports the gut microbiota parameters of elite footballers for the first time. In addition, it brings new insights into the effects of different levels of physical activity on the composition of the gut microbiota.